The Difference Of Antibacterial Power Between Cocoa Peel (Theobroma cacao L.) Extract 6,25% and Chlorhexidine 0,2% Againts Streptococcus sanguinis - Nila Murni Wulandari; Edhie Arif Prasetyo; Agus Subiwahjudi; Tamara Yuanita (Conservative Dentistry Journal, 2019)
Background: Streptococcus sanguinis is a bacterium that can cause failures in root canal treatments due its ability to penetrate the dentinal tubules to a depth of 400 μm in just two weeks. Irrigation material is needed to stop the growth of this bacteria so that no bacteria can pass through by using chemicals, irrigation materials that are widely used such as Chlorhexidine 0,2% but still lack because it cannot be used as a single irrigation solution because its effectiveness will be reduced if it is related to protein and organic dentine matrix and low Ph saliva.Therefore, research is needed to find natural ingredient that can be an alternative such as Cocoa peel extract was chosen because it contains active compounds, in the form of saponins, tanins, alkaloids, flavonoids, and terpenoids that have been known to have antibacterial properties a concentration of 6,25% is used in accordance with the MKC of Streptococcus sanguinis. Aim: To compare the antibacterial power between cocoa peel extract (Theobroma cacao L.) 6,25% and Chlorhexidine 0,2% against Streptococcus sanguinis Method: This research is an experimental laboratory with a post-test only control group design. The diffusion method was used to determine the susceptibility of bacteria isolated from the material by planting the culture of Streptococcus sanguinis on the agar medium by swabbing the nutrient media which has been divided into 3 parts consisting of negative control, cocoa peel extract and Chlorhexidine, then each nurient media so that it is given a paper disk and 0.01ml liquid on each section. The diameter of the inhibition zone was observed after 2x24 hours using the calipers. Results: The average inhibitory zone that was formed using cocoa peel extract was 20,40 mm against Streptococcus sanguinis and Chlorhexidine was 18,36 against Streptococcus sanguinis. Conclusion: Cocoa peel extract (Theobroma cacao L.) 6,25% had higher anti-bacterial power compared to 0,2% Chlorhexidine against the growth of Streptococcus sanguinis.